MANAJEMEN KONFLIK PERAN PROFESIONAL-MANAJERIAL DI KANTOR AKUNTAN PUBLIK MELALUI ORIENTASI PADA TUJUAN SISTEM DAN KEADILAN PERSEPSIAN - SITI MUTMAINAH (Jurnal Bisnis dan Akuntansi, 2003)
Historically, it was believed that dual role (i.e. the individual as professional and also involve in managerial role) can potentially have adverse consequences through the creation of role conflict. Comerford and Abernethy’s (1999) finding revealed that the individuals with a high professional orientation will experience less adverse consequences (i.e. lower role conflict) when involved in the budgeting process provided that they have taken on a system goal orientation. As such, this field study reexamines this professional-managerial role conflict with the different subject. Besides, this study is extended by looking at the moderating effect of perceived fairness on the relationship between professional orientation and role conflict. The result of this study was not consistent with those indicated by prior empirical research which showed that goal system orientation had a direct effect on the relationship between professional orientation and role conflict. This finding, however, support the contemporary perspective, which suggest that occupational commitment and organizational commitment are positively, not negatively associated. The other finding of this field study does not enable rejection of the second null hypothesis for the sample group with lower participation level. It indicates that professional-managerial conflict is reduced when professionals who have lower participation level in budgeting, have higher perceived fairness level.